2020
DOI: 10.3390/m1142
|View full text |Cite
|
Sign up to set email alerts
|

4′-(N-(Propan-1,2-dienyl)pyrrol-2-yl)-2,2′:6′,2″-terpyridine

Abstract: A new pyrrole-substituted terpyridine derivative that possesses an allene moiety was obtained as an “unexpected” sole product during an attempt to alkylate the N-atom of pyrrole with propargyl bromide in order to obtain an alkyne-functionalized terpyridine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
(29 reference statements)
1
5
0
Order By: Relevance
“…Compound 1: 1 H-NMR (CDCl 3 , 400 MHz), δ (ppm): 8.71 (m, 2H H6, 6 ), 8.65 (d, 2H, H3, 3 , J = 8.0 Hz), 8.57 (s, 2H, H3 , 5 ), 7.87 (td, 2H, H4, 4 , J = 7.6 Hz, J = 1.8 Hz), 7.34 (ddd, 2H, H5, 5 , J = 7.5 Hz, J = 4.8 Hz, J = 1.1 Hz), 7.07 (dd, 1H, Hd, J = 2.7 Hz, J = 1.8 Hz), 6.62 (dd, 1H, Hb, J = 3.7 Hz, J = 1.8 Hz), 6.32 (dd, 1H, Hc, J = 3.7 Hz, J = 2.9 Hz), 4.91 (d, 2H, He, J = 2.6 Hz), 2.45 (t, 1H, Hg, J = 2.6 Hz). 13 Compound 2: The physical and spectroscopic properties agree with those reported in the literature [13].…”
Section: Methodssupporting
confidence: 82%
See 3 more Smart Citations
“…Compound 1: 1 H-NMR (CDCl 3 , 400 MHz), δ (ppm): 8.71 (m, 2H H6, 6 ), 8.65 (d, 2H, H3, 3 , J = 8.0 Hz), 8.57 (s, 2H, H3 , 5 ), 7.87 (td, 2H, H4, 4 , J = 7.6 Hz, J = 1.8 Hz), 7.34 (ddd, 2H, H5, 5 , J = 7.5 Hz, J = 4.8 Hz, J = 1.1 Hz), 7.07 (dd, 1H, Hd, J = 2.7 Hz, J = 1.8 Hz), 6.62 (dd, 1H, Hb, J = 3.7 Hz, J = 1.8 Hz), 6.32 (dd, 1H, Hc, J = 3.7 Hz, J = 2.9 Hz), 4.91 (d, 2H, He, J = 2.6 Hz), 2.45 (t, 1H, Hg, J = 2.6 Hz). 13 Compound 2: The physical and spectroscopic properties agree with those reported in the literature [13].…”
Section: Methodssupporting
confidence: 82%
“…The molecular structure of compound 1 was unambiguously confirmed by different analytical techniques. First, the 1 H-NMR spectrum (Supplementary Material) exhibits the typical signals for the terpyridine and pyrrole sub-units as reported for other pyrrole-terpys [6,13,14,22,23]. Moreover, the acetylenic protons were characterized by a triplet and a doublet (J = 2.6 Hz) centered at 2.45 and 4.91 ppm, respectively.…”
Section: Resultsmentioning
confidence: 53%
See 2 more Smart Citations
“…In the twelfth paper, the authors reported on the synthesis of a new pyrrole-substituted terpyridine derivative that possessed an allene moiety. It was obtained as an unexpected sole product during attempts to alkylate the N-atom of pyrrole [13]. In the last paper, the serendipitous formation of the cyclic guanidinium complex poly[1,3-dimethyltetrahydropyrimidin-2(1H)-iminium [tri-µ 2 -cyanido-κ 6 C:N-dicuprate(I)]] was found during an X-ray analysis of the crystals obtained after an attempted synthesis of a copper cyanide polymer involving the diamine N,N -1,3-dimethyldiaminopropane [14].…”
mentioning
confidence: 99%